Edukasi Pemanfaatan Posyandu di Kelurahan Parak Laweh Pulau Aia Nan XX Kota Padang: Increasing the Utilization of Integrated Health Post (Posyandu) through Growth and Development Education and Family Planning in Padang City - Aldina Ayunda Insani; Laila Laila; Fitrayeni Fitrayeni; Uliy Iffah; Feni Andriani; Nada Amelinda Irya; Zulfa Safitri; Dinda Dwi Putri; Qori Mariolka Meilani; Twotri Widia Lisanda (BULETIN ILMIAH NAGARI MEMBANGUN, 2026)
Integrated Service Posts (Posyandu) are community-based primary healthcare services covering all life cycles, including toddlers and women of childbearing age. However, utilization remains suboptimal. In Padang City, toddler visit coverage reached 75.6% in 2023, below the 85% target, mainly due to limited community knowledge and awareness of Posyandu’s role. This study applied a descriptive-analytic approach through participatory educational activities integrated with the Family Oriented Midwifery Education (FOME) program in Parak Laweh Village, Padang City. Interventions included counseling, basic health examinations, growth and development monitoring using the Pre-Screening Development Questionnaire (KPSP), and education on family planning. The target group consisted of mothers with toddlers and couples of childbearing ages. Data were analyzed using univariate methods. Among 143 households, 65.22% of toddlers did not undergo routine monthly growth monitoring, 53.57% of couples of childbearing ages were not family planning participants, and 95.10% had not received prior education on child growth monitoring. Despite this, most toddlers had normal height-for-age and weight-for-age indicators. KPSP results showed that 72.72% of toddlers were developmentally appropriate, while 27.27% were categorized as questionable. Educational interventions improved community awareness and participation in Posyandu activities. However, continued efforts are required to strengthen knowledge, promote routine monitoring, and enhance the utilization of Posyandu services as a key strategy for improving maternal and child health outcomes.